Type I-conventional dendritic cells support the progression of multiple myeloma in the bone marrow - Suzuki, Sayaka; Komiya, Kazuma; Tsuda, Shogo; Yoshino, Miya; Kaisho, Tsuneyasu; Bergsagel, P. Leif; Kawamura, Koji; Fukuda, Tetsuya; Tokoyoda, Koji (Frontiers in Immunology, 2024)
Purpose: Type Ⅰ conventional dendritic cells (cDC1s) play a key role in priming anti-tumor cytotoxic T cells and inducing immune tolerance for self-antigens and tumor antigens. However, it remains unclear whether cDC1 has a protective or pathogenic role in multiple myeloma. We investigated a role of cDC1 in myeloma progression.: A myeloma mouse model was performed by intravenous transplantation of Vk*MYC myeloma cells into XCR1-Diphtheria toxin receptor (DTR) knock-in or wild-type mice. Following injection with Diphtheria toxin (DT), monoclonal (M)-proteins and myeloma cells were analyzed by ELISA and flow cytometry.Results: Here we show that inducible depletion of cDC1 after myeloma transplantation markedly suppressed the progression of myeloma in the bone marrow and extramedullary sites, such as the spleen. cDC1 appeared in the bone marrow and spleen of myeloma-transplanted mice, which highly expressed CD103 and lowly produced interleukin (IL)-12. Consequently, the frequencies of exhausted CD8 T cells and regulatory T cells significantly decreased in the bone marrow of cDC1depleted mice.Conclusions: cDC1 supports the progression of myeloma inducing exhausted CD8 T cells and regulatory T cells.